FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN INVESTASI MAHASISWA TERHADAP INSTRUMEN PASAR MODAL SYARIAH - Fadali Rahman; Salman Al-Farisi; Moh Sulton Risky; Firman Auzora A; Fathorrahman (PT. Hasba Edukasi Mandiri, 2025)
This study synthesizes and analyzes the dominant factors influencing university students’ investment interest and actual investment decisions in Islamic capital market instruments, with particular focus on the intention action gap. Using a descriptive-narrative literature review approach, data were systematically collected through the Publish or Perish application from relevant journal articles and conference proceedings published between 2021 and 2025. The selected studies were thematically analyzed to identify key patterns and research trends. The findings show that students’ Islamic investment behavior is shaped by both internal and external factors. The main internal determinants include financial literacy, intrinsic motivation, and self-efficacy, while external factors comprise social environment support, the availability of Sharia Investment Galleries (GIS) on campus, and the intensity of financial education, both formal and digital. The integration of the Theory of Planned Behavior with religiosity offers a strong conceptual framework for understanding students’ multidimensional investment behavior. As a literature-based study, this research does not empirically test causal relationships. Future studies are encouraged to employ quantitative or mixed methods. Practically, the findings emphasize the importance of integrated educational programs to bridge the gap between students’ investment intentions and real investment actions.